2016
DOI: 10.1111/hae.13128
|View full text |Cite
|
Sign up to set email alerts
|

Balance evaluation in haemophilic preadolescent patients using Nintendo Wii Balance Board®

Abstract: Tests performed indicate a poorer static postural balance in the haemophilic cohort compared to the control group. Accordingly, physiotherapy programmes, physical activity and sports should be designed to improve the postural balance with the aim of preventing joint deterioration and improving quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 29 publications
1
19
1
1
Order By: Relevance
“…This compensatory strategy was not found in haemophiliacs. Furthermore, the results of the current study support previous reports on static balance in adult and paediatric haemophilia patients, who present poorer motor control than non‐haemophilia subjects …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This compensatory strategy was not found in haemophiliacs. Furthermore, the results of the current study support previous reports on static balance in adult and paediatric haemophilia patients, who present poorer motor control than non‐haemophilia subjects …”
Section: Discussionsupporting
confidence: 91%
“…Regarding the applied methodology, accelerometers are a cheap, useful and easily portable alternative for postural control assessments in clinical practice, especially for undeveloped and developing countries. Indeed, the ACoM may be a low‐cost alternative to force platform measurements for assessing static postural control in clinical and research contexts, such as already demonstrated by the Nintendo Wii Balance Board ® …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In people with haemophilic arthropathy (PWHA), joint destruction is accompanied by changes in the musculoskeletal system such as loss of muscle force, decreased range of motion and proprioception (ie sense of joint position). 1,2 These changes negatively impact postural control in children and adults with PWHA, 3,4 resulting in an increased risk of functional deterioration and suffering new or recurrent injuries.…”
Section: Introductionmentioning
confidence: 99%
“…. The mean (std; [minimum-maximum]) total HJHS score for PWHA was 31.40(13.31; [6-55]) points, with a mean of 6.87 (4.09; [0-12]) determined for the knee and 6.13 (3.42;[2][3][4][5][6][7][8][9][10][11][12]) for the ankle. Only two PWHA presented an HJHS of 0 points in the knee, while all patients showed ankle arthropathy (HJHS > 0).…”
mentioning
confidence: 99%